The influence of jenang ayas label and packaging on customer purchase decision - Yunita Siti Mardhiyyah; Sekarsari Utami Wijaya; Dyah Satiti; Nur Lailatus Sa'diyah (AGROINTEK, 2023)
Jenang ayas is ethnic food from Gresik, East Java, Indonesia. Recently, jenang ayas are still packaged using improvised packaging, and the information conveyed regarding the product is still lacking. Even though the label information on the packaging can attract consumers' attention in making purchases, packaging will not only serve to protect the product but also as a means of promotion to increase the selling value of the product and influence the customer purchase decision. Therefore, this study aimed to examine the influence of the jenang ayas label and packaging that affect the customer purchase decision. A quantitative method with a descriptive approach was adopted following 179 responses to the online questionnaire. The finding revealed that the independent variables (label and packaging of jenang ayas) positively affected the dependent variable (customer purchase decision) both partially and simultaneously. The influence of food labels was greater than the packaging, with a value of 0.200 compared to 0.119. Label information, especially the expiration date, becomes an important factor in the jenang ayas product based on consumer choice. This study result provides useful insight into strategies for producing jenang ayas as Gresik food souvenir products in the Asian business.